2014
DOI: 10.1038/cddis.2014.219
|View full text |Cite
|
Sign up to set email alerts
|

Wnt inhibitory factor 1 suppresses cancer stemness and induces cellular senescence

Abstract: Hyperactivation of the Wingless-type (Wnt)/β-catenin pathway promotes tumor initiation, tumor growth and metastasis in various tissues. Although there is evidence for the involvement of Wnt/β-catenin pathway activation in salivary gland tumors, the precise mechanisms are unknown. Here we report for the first time that downregulation of the Wnt inhibitory factor 1 (WIF1) is a widespread event in salivary gland carcinoma ex-pleomorphic adenoma (CaExPA). We also show that WIF1 downregulation occurs in the CaExPA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(59 citation statements)
references
References 73 publications
2
57
0
Order By: Relevance
“…miR‐200c can activate the Notch signalling pathway by targeting the ligand of Notch (Jagged‐1) . Additionally, miR‐200c is associated with the increased expression of ZEB‐1, which is the direct target gene of miR‐200c, and important genes in stemness‐related Wnt pathways . Bmi1 is a key member of the Hedgehog pathway.…”
Section: Discussionmentioning
confidence: 99%
“…miR‐200c can activate the Notch signalling pathway by targeting the ligand of Notch (Jagged‐1) . Additionally, miR‐200c is associated with the increased expression of ZEB‐1, which is the direct target gene of miR‐200c, and important genes in stemness‐related Wnt pathways . Bmi1 is a key member of the Hedgehog pathway.…”
Section: Discussionmentioning
confidence: 99%
“…WNT/β-catenin signalling may play a role in regulating these cells as activity correlates with expression of CD44 in SG cancers and treatment of CICs with a WNT/β-catenin active small molecule inhibitor, LF3, blocked their self-renewal capacity (Fang et al , 2016). Indeed, WNT inhibition supresses CIC stemness and induces cellular senescence in SG squamous cell carcinoma (SCC) (Ramachandran et al , 2014), whereas activation of the WNT/β-catenin pathway, via a β-catenin gain of function approach, induces a rapidly growing, aggressive phenotype (Wend et al , 2013). While these studies did not specifically investigate the association between WNT/β-catenin and CD24/CD44 expression in SG CICs, this result suggests that dysregulated WNT/β-catenin signalling may be, at least in part, responsible for the expansion of SG CICs and tumor progression.…”
Section: Salivary Gland Developmentmentioning
confidence: 99%
“…65 Several studies have shown that inhibition of WNT signaling via modulation of β-catenin, LEF and TCF impeded the clonogenic growth of various cancer cells. [66][67][68][69][70] In addition, WNT inhibitory factor 1 (WIF1) induced cellular senescence, thereby impeding stemness and tumor growth. 67 As two recent papers have provided excellent reviews of WNT signaling and CSCs, 71,72 this review focuses on studies conducted in GBM.…”
Section: Wnt Signaling In Gbm Stemness Wnt Signaling In Stem Cellsmentioning
confidence: 99%